Interferon-α Revisited: Individualized Treatment Management Eased the Selective Pressure of Tyrosine Kinase Inhibitors on BCR-ABL1 Mutations Resulting in a Molecular Response in High-Risk CML Patients. - Vaclava Polivkova; Peter Rohon; Hana Klamova; Olga Cerna; Martina Divoka; Nikola Curik; Jan Zach; Martin Novak; Iuri Marinov; Simona Soverini; Edgar Faber; Katerina Machova Polakova (PLoS ONE)
Bone marrow transplantation or ponatinib treatment are currently recommended strategies for management of patients with chronic myeloid leukemia (CML) harboring the T315I mutation and compound or polyclonal mutations. However, in some individual cases, these treatment scenarios cannot be applied. We used an alternative treatment strategy with interferon-α (IFN-α) given solo, sequentially or together with TKI in a group of 6 cases of high risk CML patients, assuming that the TKI-independent mechanism of action may lead to mutant clone repression. IFN-α based individualized therapy decreases of T315I or compound mutations to undetectable levels as assessed by next-generation deep sequencing, which was associated with a molecular response in 4/6 patients. Based on the observed results from immune profiling, we assumed that the principal mechanism leading to the success of the treatment was the immune activation induced with dasatinib pre-treatment followed by restoration of immunological surveillance after application of IFN-α therapy. Moreover, we showed that sensitive measurement of mutated BCR-ABL1 transcript levels augments the safety of this individualized treatment strategy.